LEARNING DIFFICULTIES IN EARLY CHILDHOOD EDUCATION: ABSENCE OF AFFECTIVITY AS A DETERMINING FACTOR - Farias Santos da Silva, Adriana; Holond de Lima Rocha, Kleyton; Maria Monteiro da Silva, Gilvana; José Melo dos Santos, Mozart; Carlos Vanderlei da Silva, José; da Silva Lima, Almir; Cristina Sousa, Maryone; do Nascimento Prado, Roselândia; Pinho Neto, Gisélia; da Silva Costa, Joselma (Revista Gênero e Interdisciplinaridade, 2024)
This article aims to address concepts related to learning difficulties in Early Childhood Education, reflecting on the determining factor of these difficulties, which is the absence of affection as it is capable of influencing the teaching-learning process. Therefore, the fundamental objective of this work is to analyze learning difficulties and the importance of affectivity during learning in the process of knowledge construction. Approaches and theorists about affectivity determine the attitude about affectivity in its lived experience. Therefore, affectivity becomes important in the integral formation of human beings, as they enable different ways of acting in different learning situations, affirming the individual’s way of interacting and perceiving the world around them. Not forgetting that at school, as it is the first socializing agent outside the child’s family circle, it becomes the basis of learning to offer possibilities to make the child feel safe and protected. Therefore, for the child to have a healthy and adequate development within the school environment, and consequently in the social environment, it is necessary to establish positive interpersonal relationships, such as facilitation and support, thus enabling the success of educational objectives.